2007
DOI: 10.1002/jobm.200610285
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Azotobacter on plant roots: chemotactic response, development and analysis of root exudates of cotton (Gossypium hirsutum L.) and wheat (Triticum aestivum L.)

Abstract: Biofertilizers contribute in N(2) fixation, P solubilization, phytohormone production and thus enhance plant growth. Beneficial plant-microbe interactions and the stability and effectiveness of biofertilizer depend upon the establishment of bacterial strains in the rhizosphere of the plant. This interaction depends upon many factors, one of them being plant exudates. Root exudates are composed of small organic molecules like carbonic acids, amino acids or sugars etc., which are released into the soil and bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 7 publications
0
28
0
4
Order By: Relevance
“…ACC-deaminase enzyme bacteria are able to use ACC as the only source of nitrogen and, by reducing ethylene concentration and preventing the accumulation of this material under drought stress, can control the negative effects on root growth and, therefore, protect it (Glick et al 2007). Cotton and wheat seeds inoculated with growth promoters increased shoot and root height (Narula et al 2005;Kumar et al 2007). An increased height of Z. mays.…”
Section: Discussionmentioning
confidence: 99%
“…ACC-deaminase enzyme bacteria are able to use ACC as the only source of nitrogen and, by reducing ethylene concentration and preventing the accumulation of this material under drought stress, can control the negative effects on root growth and, therefore, protect it (Glick et al 2007). Cotton and wheat seeds inoculated with growth promoters increased shoot and root height (Narula et al 2005;Kumar et al 2007). An increased height of Z. mays.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of selected N 2 -fixing bacteria and arbuscular mycorrhizal fungi alone or in combination have shown slight to moderate benefits in increasing crop productivity and a modest capability to reduce the use of mineral fertilizers (El-Sirafy et al, 2006;Aseri et al, 2008;Gupta and Aggarwal, 2008;Jahan et al, 2013;Ansari et al, 2015). The greater benefits to crop growth seem to occur when an inoculant containing N 2 -fixing bacteria and other beneficial microorganisms is mixed with organic substrates (Nuruzzaman et al, 2003;Kumar et al, 2007;Singh et al, 2013;Kumar et al, 2014). Kumar et al (2015) showed that using a biofertilizer in the form of a super granule, containing Azotobacter chroococcum and Bacillus subtilis entrapped in an organic matrix [consisting of cow dung, rice bran, dried powder of neem leaves, and clay soil in 1:1:1:1 ratio and 25% (w/w) saresh (plant gum of Acacia sp.…”
Section: Introductionmentioning
confidence: 99%
“…The development of biological approaches to improve biofertilizers represents a unique opportunity for future generations to lower the potential economic costs and environmental impacts of current fossil-fuel-dependent industrial methods for the production of ammonia-derived fertilizers (4)(5)(6). Various laboratories have been investigating the potential of Azotobacter species to provide nitrogen to specific crops for many years, with various degrees of success (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Various laboratories have been investigating the potential of Azotobacter species to provide nitrogen to specific crops for many years, with various degrees of success (5)(6)(7)(8)(9)(10)(11). Although many nitrogen-fixing bacteria produce nitrogen in environments requiring very low oxygen, Azotobacter vinelandii has evolved the capability of fixing nitrogen as a free-living aerobe, despite the fact that nitrogenase is inherently sensitive to oxygen.…”
mentioning
confidence: 99%
See 1 more Smart Citation